Case series of four complex spinal deformities: new frontiers in pre-operative planning - Facco, Giulia; Palmisani, Rosa; Pieralisi, Massimiliano; Forcellese, Archimede; Martiniani, Monia; Specchia, Nicola; Gigante, Antonio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Osseous and medullar anomalies constitute a hard challenge for interpretation of complex vertebral deformities anatomy. To better frame these deformities three-Dimensional (3D) printing represents a new frontier in this field. The aim of this brief report is describing the use of 3D printed models for surgical planning in four complex vertebral deformity cases treatment.Methods: Four cases of severe scoliosis were treated between December 2017 and January 2019; patients’ mean age was 12,25 years. Two patients underwent neurosurgical intervention for myelomeningocele at the time of birth. Standard and dynamics X-Ray, Computed Tomography (CT) and Magnetic Resonance (MR) of the column were performed pre-operatively. CT files were implemented to build the 3D model of each spine and selected ribs. The models were 3D printed in thermoplastic material, then used to study the deformities and for surgical planning. A survey proposal about 3D models’ utility and accuracy has been made to 15 residents and 6 main surgeons.Results: Preparation of each 3D models required about 316.5 minutes and printing time was about 108 hours each. The average cost was 183.16 € to produce one 3D printed model, which resulted useful in surgical planning and educational.Conclusions: The manufacture of 3D models requires time, resources and multidisciplinary approach, it must be justified by complexity of the case. In this study 3D Printing allowed surgeons to carefully plan and simulate the surgery, ensuring for a better sizing of the implant.